Community Medicine Outpatient Department: Patient profile and reasons for bypass of lower-level public health facilities - Kumar, Sanjeev; Jain, Seema; Varghese, Anila; Gautam, Neelam S; Gupta, Ramesh Chand (Indian Journal of Community Health, 2023)
Background: The General OPD under the department of Community Medicine at LLRM Medical College, Meerut was inaugurated with the vision to improve quality of OPD services by reducing the patient burden and waiting time at specialist OPDs. Aim & Objective: To describe the profile of patients attending the Community Medicine OPD in LLRM Medical College, Meerut and to estimate the extent and reasons for bypass of lower-level public health facility by patients attending the general OPD. Settings and Design: A hospital based descriptive study was conducted in the general OPD. Methods and Material: Data of all patients from 1st July,2023 to 31st August,2023 was collected from the registers maintained in the OPD. A sample of 215 patients were selected by systematic random sampling to study the objective to assess bypass of lower-level public health facility. Statistical analysis used: Descriptive statistics. Results: A total of 2570 patients attended the general OPD from 1st July,2023 to 31st August,2023. Around 12.8% patients required referral to specialist OPDs. Most common presenting complaints were respiratory symptoms (29.8%). It was seen that 58.8% patients had bypassed the lower-level public health system and the most common reasons were non-availability of a facility nearby (26.8%), not satisfied with previous experience (23.7%), non-availability of treatment (21.6%) and investigations (17.5%), and lack of awareness of services available at the public health facility (15.4%). Conclusions: The general OPD serves as a model for other medical colleges to emulate and improve the quality of services at tertiary care centres.